High-performance supramolecular hydrogel for hemostasis and wound closure and preparation method of high-performance supramolecular hydrogel
By copolymerizing four-fold hydrogen-bonded monomers with acrylic monomers and combining them with bioactive components, the problems of easy swelling and insufficient mechanical strength of polyacrylic acid hydrogels in humid environments were solved, and a supramolecular hydrogel with both high adhesion and mechanical properties was prepared for rapid hemostasis and wound closure.
Patent Information
- Application Number
- CN202410747488.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2025-12-12
AI Technical Summary
Existing polyacrylic acid-based adhesive hydrogels are prone to swelling and leakage in humid environments, and it is difficult to balance mechanical strength and adhesion properties, which limits their application in tissue bonding.
A hierarchical, multi-hydrogen-bonded supramolecular hydrogel was formed by copolymerizing a four-hydrogen-bonded monomer with an acrylic monomer without emulsifiers or chemical crosslinking agents. Combined with the bioactive component epigallocatechin gallate, a hydrogel with high adhesion and mechanical properties was constructed.
It achieves good adhesion and mechanical strength in humid environments, and possesses excellent cell compatibility, antioxidant and antibacterial properties, as well as rapid hemostasis and wound closure capabilities.
Smart Images

Figure CN121102553A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of biomaterials, more particularly to a high-performance supramolecular hydrogel for rapid hemostasis and wound closure and a preparation method thereof. BACKGROUND
[0002] The rapid establishment of a flexible biological interface between biological adhesives and tissue surfaces is a key feature of excellent tissue adhesives, but due to the moist and dynamic characteristics of the complex physiological environment, effective tissue reconnection remains a challenging task. Synthetic polyacrylic-based hydrogels have abundant carboxyl functional groups, which are conducive to tissue adhesion, and have been widely studied and made great progress as adhesive hydrogels for hemostasis control and wound closure. However, polyacrylic-based adhesive hydrogels are still hindered by some limitations in actual internal tissue connection applications. Polyacrylic-based adhesive hydrogels may be over-hydrated and swollen in a water environment due to the presence of a large number of carboxyl groups, resulting in poor wet adhesion of the gel, so that leaking body fluids or blood may cause the gel to detach from the wound, which limits the application of polyacrylic-based adhesive hydrogels in a moist physiological environment. Therefore, it is necessary to overcome the over-hydration and swelling behavior of polyacrylic-based adhesive hydrogels, improve the wet adhesion performance of the gel, and resist the leakage of body fluids, blood, etc. The common strategies currently include introducing hydrophobic components and emulsifiers through emulsion polymerization or introducing organic solvents for organic phase polymerization, as well as constructing asymmetric multi-layer hydrogels to limit the swelling behavior of the polyacrylic swelling layer with a low swelling layer. Although these methods are effective, they are also accompanied by a series of defects, including the introduction of emulsifiers and organic solvents increasing material toxicity, complex preparation process, poor interface connection, and inconvenience of use, etc. Therefore, it is necessary to prepare low-toxicity, high-adhesion, and low-swelling hydrogels without introducing undesirable components using a simple preparation process.
[0003] In addition, the practical application of polyacrylic-based adhesive hydrogels has always been hindered by the typical trade-off between mechanical strength and adhesion performance. Generally, the damaged tissue surface is not static, but remains in a deformed state under different strains, such as bulging, bending, and stretching, etc. Due to the lack of significant dynamic compliance and mechanical strength, polyacrylic-based hydrogel patches inevitably accumulate stress during repeated deformation, leading to the eventual failure of the interface. In view of this, it is also important to improve the mechanical properties of polyacrylic-based hydrogel patches. However, there is a contradiction between the mechanical strength and adhesion performance of polyacrylic-based hydrogel patches, making it difficult to achieve both. Therefore, it is imperative to design polyacrylic hydrogel patches with high adhesion and strong mechanical properties, to coordinate the balance between adhesion and mechanical properties, and to further broaden the range of practical applications. SUMMARY
[0004] The present application aims to overcome the shortcomings of the existing polyacrylic acid-based adhesive hydrogel, and provide a low-toxicity, high-adhesion and mechanical performance, low-swelling, high-performance supramolecular hydrogel for rapid hemostasis and wound closure, and a preparation method and application thereof.
[0005] The technical purpose of the present application is achieved by the following technical scheme.
[0006] A high-performance supramolecular hydrogel for hemostasis and wound closure and a preparation method thereof are carried out according to the following steps:
[0007] The acrylic monomer and the tetra-hydrogen bond-based monomer 4-(6-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)-acrylic acid ethyl ester are uniformly dispersed in deionized water, and a photoinitiator is added to form a polymerization precursor solution; the polymerization precursor solution is placed in a reaction container for photoinitiated polymerization; the copolymer hydrogel obtained by polymerization is impurity-removed, then soaked in a water-soluble epigallocatechin gallate solution of a bioactive component, and then soaked in deionized water for equilibrium.
[0008] In the technical scheme of the present application, the molar ratio of the total amount of the two monomers and the amount of the tetra-hydrogen bond-based monomer (HEA-UPy) is 100:(1-5), preferably 100:(3-5), i.e. the ratio of the total amount of substance of the two monomers (i.e. the acrylic monomer and the tetra-hydrogen bond-based monomer) and the amount of substance of the tetra-hydrogen bond-based monomer; in the polymerization precursor solution, the concentration of the two monomers is 5-10 mol / L, i.e. the amount of the two monomers is converted into the sum of the amount of substance, and then divided by the volume of deionized water.
[0009] In the technical scheme of the present application, 2-hydroxy-2-methyl-1-phenyl-1-propanone (IRGACURE 1173) is selected as the photoinitiator, and the amount thereof is 0.1-0.5 mol% of the sum of the amount of substance of the two monomers, preferably 0.1-0.25 mol%.
[0010] In the technical scheme of the present application, the reaction container is a glass mold with silica gel sheets spaced apart, and the thickness of the silica gel sheets is 0.5-2 mm.
[0011] In the technical scheme of the present application, the photoinitiated polymerization time is 0.5-2 h, preferably 0.5-1 h.
[0012] In the technical scheme of the present application, the photoinitiated polymerization temperature is room temperature 20-30 degrees Celsius.
[0013] In the technical solution of the present application, in the epigallocatechin gallate aqueous solution, the concentration of epigallocatechin gallate is 0.1%-0.8% w / v, preferably 0.5-0.8% w / v, i.e. the mass (unit: g) of epigallocatechin gallate / the volume (unit: ml) of deionized water x 100%.
[0014] In the technical solution of the present application, after the polymerization is completed, the copolymer hydrogel obtained by demolding is directly immersed in deionized water for one day (20-24 hours) to remove unreacted small molecules and / or other impurities.
[0015] In the technical solution of the present application, the immersion time in the epigallocatechin gallate aqueous solution is 4-10 h, preferably 6-10 h; and the temperature is room temperature 20-30 degrees Celsius.
[0016] In the technical solution of the present application, the quadruple hydrogen bond-based monomer 4-(6-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)-acrylic acid ethyl ester is prepared according to the following steps:
[0017] In the presence of dibutyltin dilaurate and chloroform, a mixture of 2(6-isocyanatohexylaminocarbonylamino)-6-methyl-4[1H]pyrimidinone and 2-hydroxyethyl acrylate is stirred and reacted under a nitrogen atmosphere and heating conditions; after the reaction is completed, the mixture is cooled to room temperature, the residual solid is filtered off under reduced pressure, the obtained filtrate is precipitated into n-hexane, the precipitate is collected and dried overnight under vacuum, thereby obtaining the hydrophobic quadruple hydrogen bond-based monomer 4-(6-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)-acrylic acid ethyl ester (HEA-UPy), wherein dibutyltin dilaurate is used as a catalyst, the amount of which is 5-20 uL, chloroform is used as a solvent, the amount of which is 100-300 mL, n-hexane is used as a precipitant, the amount of which is 800-2000 mL, and the molar ratio of 2(6-isocyanatohexylaminocarbonylamino)-6-methyl-4[1H]pyrimidinone (UPy-NCO) to 2-hydroxyethyl acrylate (HEAA) is 1:(1.1-2), preferably 1:(1.1-1.5); the reaction temperature is 45-70°C, preferably 50-60°C; and the reaction time is 8-20 h, preferably 12-15 h.
[0018] The technical scheme of the present application is that the isocyanate group in 2(6-isocyanohexyl aminocarbonyl amino)-6-methyl-4[1H] pyrimidinone (UPy-NCO) reacts with the hydroxyl group in 2-hydroxyethyl acrylate (HEAA) to synthesize a functional monomer 4-(6-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl) ureido) hexyl carbamoyloxy)-acrylic acid ethyl ester (HEA-UPy), which is composed of an acrylic acid head, a hydrophobic alkyl spacer connected by a carbamate, and a self-complementary 2-2-ureido-4-pyrimidinone (UPy) motif, and can produce abundant hydrophobic association and quadruple hydrogen bonds; then the obtained HEA-UPy monomer is copolymerized with a hydrophilic acrylic acid (AAc) monomer without using any emulsifier and chemical crosslinking agent, and the monomer copolymerization is initiated by a photoinitiator IRGACURE 1173, and then a biologically active epigallocatechin gallate (EGCG) is physically introduced to obtain a hierarchical multiple hydrogen bond crosslinked supramolecular hydrogel (AUE).
[0019] The present application provides a high-performance supramolecular hydrogel which can be used for rapid hemostasis and wound closure and a preparation method thereof, the preparation method is simple, no emulsifying emulsifier or organic solvent is used in the gel preparation process, and no chemical crosslinking agent is introduced, and a supramolecular hydrogel with a hierarchical multiple hydrogen bond (single, double, and quadruple) crosslinked network structure is obtained by in-situ copolymerization of a self-complementary 4-(6-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl) ureido) hexyl carbamoyloxy)-acrylic acid ethyl ester monomer and an acrylic acid monomer and physical doping of a biologically active component epigallocatechin gallate.
[0020] The existence of various single, double, and quadruple hydrogen bonds widens the distribution of the physical crosslinking binding strength, so that the hydrogel realizes a win-win of mechanical properties and adhesion properties, and has excellent mechanical properties and adhesion properties, including excellent elongation at break, high tensile stress, ultrahigh toughness, rapid and strong wet tissue adhesion strength, relatively high burst pressure, and durability and reversible adhesion under cyclic loading. At the same time, the introduction of EGCG also enables the gel to obtain various biological activity functions, and the AUE-3 supramolecular hydrogel has excellent cell compatibility, antioxidant and antibacterial properties and the like. The supramolecular hydrogel patch exhibits excellent hemostasis and wound closure ability in rat liver puncture, incision models and full-thickness skin incision models. BRIEF DESCRIPTION OF DRAWINGS
[0021] Figure 1 It is a technical scheme flow diagram of the present application.
[0022] Figure 2is the preparation and characterization graph of 4-(6-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl) ureido) hexylcarbamoyloxy)-acrylic acid ethyl ester (HEA-UPy) monomer in the application.
[0023] Figure 3 is the mechanical property characterization graph of the supramolecular hydrogel used in the animal experiment in the application.
[0024] Figure 4 is the adhesion property characterization graph of the supramolecular hydrogel used in the animal experiment in the application to pig skin tissue.
[0025] Figure 5 is the swelling behavior characterization graph of the supramolecular hydrogel used in the animal experiment in the application.
[0026] Figure 6 is the burst pressure and hemostatic performance characterization graph of the supramolecular hydrogel used in the animal experiment in the application.
[0027] Figure 7 is the wound closure performance characterization graph of the supramolecular hydrogel used in the animal experiment in the application. DETAILED DESCRIPTION
[0028] The technical solutions of the application will be further described below through specific examples. The drugs used in the examples of the application are shown in the following table:
[0029]
[0030] Example 1
[0031] Step 1, weigh 5.5g 2-hydroxyethyl acrylate (HEAA), 8.8g 2(6-isocyanohexyl aminocarbonylamino)-6-methyl-4[1H] pyrimidinone (UPy-NCO), and appropriate amount of chloroform into a three-necked flask, drop in 2 drops of dibutyltin dilaurate, vacuumize and fill with nitrogen for multiple times, heat to 60℃ to start the reaction, and the reaction time is 10h.
[0032] Step 2, after the reaction is completed, the reaction liquid is filtered under reduced pressure to remove the residual solid, the filtrate is poured into 20 times the volume of n-hexane for precipitation, and the precipitate is further filtered under reduced pressure to obtain white solid, which is 4-(6-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl) ureido) hexylcarbamoyloxy)-acrylic acid ethyl ester (HEA-UPy) monomer.
[0033] Step 3, 0.69 g of acrylic acid, 0.12 g of HEA-UPy were weighed and dissolved in an appropriate amount of deionized water to form a clear and transparent monomer solution, 10 uL of 2-hydroxy-2-methyl-1-phenyl-1-propanone was added dropwise, mixed uniformly, injected into the mold with two glass sheets spaced by a 1 mm thick silica gel sheet using a syringe, and sealed, and moved into the ultraviolet crosslinking box for photo-induced polymerization for 1 h. After the polymerization was completed, the mold was removed, and the gel was soaked in deionized water for one day to remove unreacted small molecules.
[0034] Step 4, 0.5 g of epigallocatechin gallate (EGCG) was weighed on a balance and dissolved in 100 mL of deionized water, and a uniform solution was prepared by ultrasonic. Then the gel sheet obtained in step 3 was soaked in a fresh EGCG aqueous solution for 6 hours, and then immersed in deionized water for 24 hours, and finally the final supramolecular hydrogel (AUE-3) patch was obtained.
[0035] Example 2
[0036] Step 1, 5.5 g of 2-hydroxyethyl acrylate (HEAA) and 8.8 g of 2(6- isocyanatohexylaminocarbonylamino)-6-methyl-4[1H]pyrimidinone (UPy-NCO) were weighed on a balance and placed in a three-necked flask, 2 drops of dibutyltin dilaurate were added, and the reaction was carried out by vacuum and nitrogen multiple times at 60°C. The reaction time was 10 h.
[0037] Step 2, after the reaction was completed, the reaction liquid was filtered under reduced pressure to remove the residual solid, the filtrate was poured into 20 times the volume of n-hexane to precipitate, and the precipitate was further filtered under reduced pressure to obtain white solid, which was 4-(6-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)-acrylic acid ethyl ester (HEA-UPy) monomer.
[0038] Step 3, 0.71 g of acrylic acid and 82 mg of HEA-UPy were weighed and dissolved in an appropriate amount of deionized water to form a clear and transparent monomer solution, 10 uL of 2-hydroxy-2-methyl-1-phenyl-1-propanone was added dropwise, mixed uniformly, injected into the mold with two glass sheets spaced by a 1 mm thick silica gel sheet using a syringe, and sealed, and moved into the ultraviolet crosslinking box for photo-induced polymerization for 1 h. After the polymerization was completed, the mold was removed, and the gel was soaked in deionized water for one day to remove unreacted small molecules.
[0039] Step 4, 0.5 g of epigallocatechin gallate (EGCG) was weighed on a balance and dissolved in 100 mL of deionized water, and a uniform solution was prepared by ultrasonic. Then the gel sheet obtained in step 3 was soaked in a fresh EGCG aqueous solution for 6 hours, and then immersed in deionized water for 24 hours, and finally the final supramolecular hydrogel (AUE-2) patch was obtained.
[0040] Example 3
[0041] Step 1, 5.5g of 2-hydroxyethyl acrylate (HEAA), 8.8g of 2(6- isocyanatohexylaminocarbonylamino)-6-methyl-4[1H]pyrimidinone (UPy-NCO), an appropriate amount of chloroform were weighed on a balance and placed in a three-necked flask, 2 drops of dibutyltin dilaurate were added dropwise, vacuum was repeatedly applied and nitrogen was introduced, and the reaction was started by heating at 60°C. The reaction time was 10h.
[0042] Step 2, after the reaction was completed, the reaction liquid was filtered under reduced pressure to remove the residual solid, the filtrate was poured into 20 volumes of n-hexane to precipitate, and the precipitate was further filtered under reduced pressure to obtain white solid, which was 4-(6-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)-acrylic acid ethyl ester (HEA-UPy) monomer.
[0043] Step 3, 0.68g of acrylic acid and 0.21g of HEA-UPy were weighed, an appropriate amount of deionized water was added to dissolve them, forming a clear and transparent monomer solution, 10Ul of 2-hydroxy-2-methyl-1-phenyl-1-propanone was added dropwise, mixed uniformly, and injected into a mold with two glass sheets separated by a 1mm thick silica gel sheet using a syringe, and sealed, and then moved into a UV crosslinking box for photo-induced polymerization for 1h. After the polymerization was completed, the mold was removed, and the gel was soaked in deionized water for one day to remove unreacted small molecules.
[0044] Step 4, 0.5g of epigallocatechin gallate (EGCG) was weighed on a balance and dissolved in 100mL of deionized water to form a uniform solution by ultrasonic treatment. Then the gel sheet obtained in step 3 was soaked in fresh EGCG aqueous solution for 6 hours, and then immersed in deionized water for 24 hours, and the final supramolecular hydrogel (AUE-5) patch was obtained after the end of the soaking.
[0045] Continued preparation of supramolecular hydrogel (AUE) patch: acrylic acid monomer (AAc) and quadruple hydrogen bond-based monomer (HEA-UPy) were dissolved in deionized water, initiator 2-hydroxy-2-methyl-1-phenyl-1-propanone (IRGACURE 1173) was added, and the mixture was dissolved to form a transparent and clear polymer precursor solution. Subsequently, the polymer precursor solution was injected into the glass mold with silica gel sheet spacing by a syringe, and then photo-initiated polymerization was carried out in a crosslinking box. After the polymerization was completed, the obtained copolymer hydrogel was directly immersed in deionized water for one day to remove unreacted small molecules, and then immersed in a bioactive component solution of epigallocatechin gallate in water, and then immersed in deionized water for equilibrium, to obtain AUE-x (x = 1, 2, 3, 4, 5) supramolecular hydrogel. The hydrogel without EGCG aqueous solution immersion was used as a control group, and was recorded as AU-x (x = 1, 2, 3, 4, 5) hydrogel. The x in AUE-x and AU-x represents the percentage of the amount of substance of HEA-UPy monomer in the total amount of substance of two monomers (i.e. acrylic acid monomer and quadruple hydrogen bond-based monomer). For example, if x is 5, the percentage of the amount of substance of HEA-UPy monomer in the total amount of substance of two monomers is 5%, that is, the amount of substance of HEA-UPy monomer is 5, and the amount of substance of acrylic acid monomer is 95.
[0046] As shown in Figure 1 , the network formation and formula composition of the supramolecular hydrogel used in animal experiments in the present application, (a) corresponds to the preparation process of AUE hydrogel, (b) corresponds to the molecular structure of the copolymerization of AAc / HEA-UPy precursor aqueous solution to form supramolecular polymer without the participation of chemical crosslinking agent and surfactant, (c) corresponds to the schematic structure of hierarchical multiple hydrogen bond crosslinking network, which includes quadruple bond, double bond and single bond hydrogen bond.
[0047] As shown in Figure 2 , the preparation and characterization of 4-(6-(3-(6-methyl-4-oxo-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)-acrylic acid ethyl ester (HEA-UPy) monomer in the present application, (a) corresponds to the preparation equation of HEA-UPy; (b) corresponds to the nuclear magnetic test results of HEA-UPy, the single peak at 13.13 ppm corresponds to NH (h1) on the UPy unit, the two single peaks at 11.88, 10.11 ppm correspond to NH (h2, h3) on the urea group, and the absorption peak at 5.05-4.98 ppm represents NH (h4) on the carbamate group.
[0048] Mechanical property testing of supramolecular hydrogels: The prepared supramolecular hydrogels were tested using an electronic universal testing machine (Instron, USA): rectangular tensile samples (length: 30 mm, width: 2 mm, thickness: 1 mm) were subjected to tensile testing at a strain rate of 50 mm / min. The strain step increase range of the cyclic tensile loading-unloading test was 1-10, with a fixed strain of 5 and a strain rate of 50 mm / min.
[0049] Adhesion performance testing of supramolecular hydrogels: Pigskin was selected as the adhesion substrate, and tensile-shear tests (ASTM F2255) were conducted using an electronic universal testing machine (Instron, USA) to evaluate the adhesion performance of the AUE hydrogel. The hydrogel was cut into 10×10×1mm pieces. 3 The sample was sandwiched between two pieces of cut pigskin, with a bonding area of 10×10mm. 2 The wet adhesion properties of the hydrogel-adhered pigskin tissue were determined by immersing it in deionized water or a high-humidity environment for a certain period of time, followed by a tensile-shear test.
[0050] like Figure 3As shown, the mechanical properties of the supramolecular hydrogels used in the animal experiments of this invention are characterized. (a) The intuitive mechanical properties of the AUE-3 hydrogel: The prepared AUE-3 hydrogel is transparent, flexible, stretchable, conformal, and puncture-resistant. The AUE-3 hydrogel can withstand various deformations, such as stretching more than 15 times without significant breakage, and can resist puncture by a 1mL pipette tip. It adheres well to uneven skin surfaces. (b) The stress-stress properties of the AUE-x (x=1, 2, 3, 4, 5) hydrogels are also shown. The test results show that as the amount of HEA-UPy increases, the tensile stress-strain curve of the AUE hydrogel becomes closer to the J-shaped curve with strain-hardening characteristics; (c) Test results of tensile strength, elongation at break, toughness and Young's modulus of AUE-x (x=1, 2, 3, 4, 5) hydrogels—Radar shows that all AUE hydrogels have high elongation, from 1160% of AUE-5 to 2320% of AUE-1, with the self-complementary 2-2-urea- The increase in 4-pyrimidinone (UPy) content leads to a corresponding increase in tensile stress. A critical value is defined as 3 mol.% UPy content. AUE hydrogels with UPy content below 3 mol.% exhibit relatively low fracture strength, Young's modulus, and fracture toughness, while those with UPy content above 3 mol.% show only slightly higher values, but with reduced tensile strength. (d) Load-unloading tensile test results for AUE-3 hydrogel under different strains (1-10). Under different strains (1-10), AUE-3 hydrogel did not exhibit significant mechanical hysteresis during continuous loading-unloading. (e) Total energy, dissipated energy, and dissipation rate of each cycle curve for AUE-3 hydrogel under different strains (1-10). As the strain gradually increases from 1 to 10, the dissipated energy of AUE-3 hydrogel gradually increases from 0.01 to 0.7 MJ / m³, with a relatively low dissipation rate, all below 20%, indicating good elasticity and high reversibility of the gel under various deformations.
[0051] like Figure 4As shown, the adhesion properties of the supramolecular hydrogels used in the animal experiments of this invention to porcine skin tissue are as follows: (a) the overlap shear stress-displacement test results of AUE-x (x = 1, 2, 3, 4, 5) hydrogels to wet porcine skin tissue; (b) the overlap shear adhesion strength of AUE-x (x = 1, 2, 3, 4, 5) hydrogels to wet porcine skin tissue. With the increase of UPy content, the overlap shear adhesion strength of AUE hydrogels to wet porcine skin tissue first increases and then decreases, reaching the maximum value (263.2 ± 12.6 kPa) in the AUE-3 hydrogel group; (c) the overlap shear stress-displacement test results of AUE-3 hydrogels to porcine skin tissue in different humid environments; (d) the overlap shear stress-displacement test results of AUE-3 hydrogels to porcine skin tissue in different humid environments. The AUE-3 hydrogel exhibits strong and durable underwater adhesion to pigskin tissue under different humid environments. Immersion in water for 12 hours and placement under high humidity conditions for 12 hours have no significant effect on the adhesion strength. Even after immersion in water for 24 hours, the lap shear adhesion strength with pigskin can still reach 182.4 ± 29.1 kPa, indicating that the AUE-3 hydrogel also exhibits strong and durable underwater adhesion in different humid environments. (e) The lap shear stress test results of the AUE-3 hydrogel on wet pigskin tissue under 1000 loading-unloading cycles at 50% tensile strain show that the AUE-3 hydrogel exhibits strong and repeatable adhesion on pigskin, maintaining at least 1000 tensile-shear deformations without significant weakening of the lap shear strength.
[0052] Animal experiments using supramolecular hydrogels to control hemostasis in a rat liver puncture and incision model: Male rats weighing 200-300g were selected for liver injury hemostasis experiments. Before surgery, heparin (3000U / kg) was injected intraperitoneally for anticoagulation, followed by anesthesia with sodium pentobarbital and fixation to a surgical board. The liver was then exposed through an abdominal incision. Blood on the liver surface was wiped clean, and a filter paper was placed under the liver to absorb blood from the wound. The rat liver puncture model was performed using a 26-G needle. A linear incision model of the rat liver was established by making a 10mm long and 5mm deep incision on the liver lobe with a scalpel. AUE hydrogel was immediately applied to the bleeding site to seal the wound. The control group received no treatment. The entire process was recorded with a camera, including hemostasis time, to assess hemostatic ability. Blood loss was calculated by comparing the weight of the filter paper before and after the experiment. All measurements were repeated four times.
[0053] Animal experiments using supramolecular hydrogels to establish a full-thickness skin incision model for wound closure: Male rats weighing 200-300g were used to establish a full-thickness skin incision model to evaluate the wound-closure performance of the hydrogel. After anesthesia with sodium pentobarbital, hair was collected from the back of the rats and disinfected with povidone-iodine. A 2cm full-thickness skin incision was made on the back of each rat using a scalpel. A strip of AUE hydrogel (30mm × 10mm × 1mm) was applied to the incision to close the wound. Controls were treated with PBS and sutured using conventional methods. Wound closure was observed using a digital camera on postoperative days 1, 3, and 7. Rats were sacrificed on postoperative day 7, and the skin around the wound was collected for histological evaluation.
[0054] like Figure 5 As shown, the swelling behavior of supramolecular hydrogels used in animal experiments in this invention is illustrated. (a) shows the water content change test results of AUE-x (x=1,2,3,4,5) hydrogels after 14 days of immersion in deionized water. During the 14-day immersion process, the water content of AUE-3 hydrogel did not change much. Compared with AUE-1 and AUE-2 hydrogels, AUE-3 showed significantly stable swelling kinetics. (b) shows that even after immersion in water for 14 days, AUE-3 hydrogel still maintained a swelling size similar to its initial state.
[0055] like Figure 6 As shown, the burst pressure and hemostatic properties of the supramolecular hydrogel used in the animal experiments of this invention are as follows: (a) shows the burst pressure test results of AUE-3 hydrogel, commercial hydrogel, and AU-3. The burst pressure of AUE-3 hydrogel is as high as 108±9 kPa, which is significantly higher than that of the two commercial hydrogel adhesives (Vetbond). TM and Fibrin glue TM (a) Bursting pressure of AUE-3 hydrogel and AU-3 hydrogel, AUE-3 hydrogel showed good internal tissue sealing ability; (b) Comparison of bleeding volume between AUE-3 hydrogel and control group in liver puncture and liver incision surgery, the total blood loss of the control group liver puncture model and liver incision model was 312±37.3 mg and 653±72.6 mg, respectively, while the total blood loss of AUE-3 group was significantly reduced, at 35±7.6 mg and 50±8.7 mg, respectively, indicating that AUE-3 hydrogel has excellent hemostatic ability; (c) Bloodstains on filter paper at certain time intervals between AUE-3 hydrogel and control group in liver puncture and liver incision surgery, the control group liver puncture model and liver incision model showed abundant bloodstains, while the bloodstains of AUE-3 hydrogel group were not obvious, indicating that AUE-3 hydrogel can effectively stop liver injury bleeding.
[0056] like Figure 7As shown, the wound-closure performance of the supramolecular hydrogel used in the animal experiments of this invention is as follows: (a) corresponding to the wound closure at different time points after rinsing with phosphate-buffered saline (PBS), suturing, and treatment with AUE-3 hydrogel, respectively. The wound incision in the AUE-3 group gradually disappeared, and the wound was completely closed with a smooth and neat surface by day 7. In stark contrast, the wound closure in the PBS group failed, with obvious blood crusts and scars, and the wound closure in the suturing group was delayed, with obvious scars; (b) corresponding to the distance between the epidermis and dermis after wound closure after rinsing with phosphate-buffered saline (PBS), suturing, and treatment with AUE-3 hydrogel, respectively. The epidermis and dermis lengths in the AUE-3 group were the shortest. Seven days after wound closure, the AUE-3 group showed the shortest distance between the epidermis and dermis. The dermal distance in the three groups was 0.1 mm, significantly lower than that in the PBS group and the suture group; (c) Hematoxylin-eosin (H&E) staining of wound sections after rinsing with phosphate-buffered saline (PBS), suturing, and AUE-3 hydrogel treatment, respectively. Scale bar: 1 mm. The epidermis in the AUE-3 group was intact and completely regenerated. In the PBS group, obvious scarring and disordered fibrous tissue were visible on the top of the epidermis. The epidermis in the suture group appeared intact, but the glandular lumen did not regenerate, possibly indicating intercellular edema and secondary wounds from the suture needles. In addition, compared with other groups, the AUE-3 group showed no obvious inflammatory response, and the dermal incision edge had almost no gaps, indicating better tissue regeneration. In summary, the results show that the AUE-3 group has the best wound closure and repair effect.
[0057] By adjusting the process parameters according to the present invention, hydrogels can be prepared, and tests have shown that they exhibit performance essentially consistent with that of the present invention. The present invention has been described above as exemplary. It should be noted that any simple modifications, alterations, or other equivalent substitutions that can be made by those skilled in the art without creative effort, without departing from the core of the present invention, fall within the protection scope of the present invention.
Claims
1. A high-performance supramolecular hydrogel for hemostasis and wound closure, characterized in that, The following steps were performed: Acrylic acid monomer and tetrahydrobonded monomer 4-(6-(3-(6-methyl-4-oxy-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)ethyl acrylate were uniformly dispersed in deionized water, and a photoinitiator was added to form a polymerization precursor solution; the polymerization precursor solution was placed in a reaction vessel for photoinitiated polymerization; the copolymer hydrogel obtained by polymerization was purified, then soaked in an aqueous solution of the bioactive component epigallocatechin gallate, and then soaked in deionized water to equilibrate; the molar ratio of the total amount of the two monomers and the amount of tetrahydrobonded monomer 4-(6-(3-(6-methyl-4-oxy-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)ethyl acrylate was 100:(1-5), and the concentration of the two monomers in the polymerization precursor solution was 5-10 mol / L.
2. The high-performance supramolecular hydrogel for hemostasis and wound closure according to claim 1, characterized in that, The molar ratio of the total amount of the two monomers and the amount of the tetrahydrobonded monomer 4-(6-(3-(6-methyl-4-oxy-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)ethyl acrylate is 100:(3-5); the concentration of the two monomers in the prepolymerization solution is 8-10 mol / L.
3. A high-performance supramolecular hydrogel for hemostasis and wound closure according to claim 1 or 2, characterized in that, The tetrahydrobonded monomer 4-(6-(3-(6-methyl-4-oxy-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)ethyl acrylate is prepared according to the following steps: In the presence of dibutyltin dilaurate and chloroform, a mixture of 2(6-isocyanohexylaminocarbonylamino)-6-methyl-4[1H]pyrimidinone and 2-hydroxyethyl acrylate was stirred and reacted under nitrogen atmosphere and heating. After the reaction was completed, the mixture was cooled to room temperature, the residual solid was filtered off under reduced pressure, the filtrate was precipitated into n-hexane, the precipitate was collected and dried overnight under vacuum to obtain the hydrophobic tetrahydrobonded monomer 4-(6-(3-(6-methyl-4-oxy-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)ethyl acrylate (HE The reaction mixture (A-UPy) is prepared in the following manner: dibutyltin dilaurate is used as a catalyst at a concentration of 20-100 μL; chloroform is used as a solvent at a concentration of 100-300 mL; n-hexane is used as a precipitant at a concentration of 800-2000 mL; the molar ratio of 2(6-isocyanohexylaminocarbonylamino)-6-methyl-4[1H]pyrimidinone (UPy-NCO) to 2-hydroxyethyl acrylate (HEAA) is 1:(1.1-2), preferably 1:(1.1-1.5); the reaction temperature is 45-70 °C, preferably 50-60 °C; and the reaction time is 8-20 h, preferably 12-15 h.
4. A high-performance supramolecular hydrogel for hemostasis and wound closure according to claim 1 or 2, characterized in that, 2-Hydroxy-2-methyl-1-phenyl-1-propanone is selected as the photoinitiator, and its amount is 0.1-0.5 mol% of the sum of the two monomers, preferably 0.1-0.25 mol%. The photoinitiation polymerization time is 0.5-2 h, preferably 0.5-1 h. The photoinitiation polymerization temperature is room temperature, 20-30 degrees Celsius. In the aqueous solution of epigallocatechin gallate, the concentration of epigallocatechin gallate is 0.1%-0.8% w / v, preferably 0.5-0.8% w / v. The soaking time in the aqueous solution of epigallocatechin gallate is 4-10 h, preferably 6-10 h. The temperature is room temperature, 20-30 degrees Celsius.
5. A high-performance supramolecular hydrogel for hemostasis and wound closure according to claim 1 or 2, characterized in that, The reaction vessel is a glass mold with silicone sheets spaced apart, the silicone sheets being 1.5–2 mm thick.
6. A method for preparing a high-performance supramolecular hydrogel for hemostasis and wound closure, characterized in that, The following steps were performed: Acrylic acid monomer and tetrahydrobonded monomer 4-(6-(3-(6-methyl-4-oxy-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)ethyl acrylate were uniformly dispersed in deionized water, and a photoinitiator was added to form a polymerization precursor solution; the polymerization precursor solution was placed in a reaction vessel for photoinitiated polymerization; the copolymer hydrogel obtained by polymerization was purified, then soaked in an aqueous solution of the bioactive component epigallocatechin gallate, and then soaked in deionized water to equilibrate; the molar ratio of the total amount of the two monomers and the amount of tetrahydrobonded monomer 4-(6-(3-(6-methyl-4-oxy-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)ethyl acrylate was 100:(1-5), and the concentration of the two monomers in the polymerization precursor solution was 5-10 mol / L.
7. The method for preparing a high-performance supramolecular hydrogel for hemostasis and wound closure according to claim 6, characterized in that, The molar ratio of the total amount of the two monomers and the amount of the tetrahydrobonded monomer 4-(6-(3-(6-methyl-4-oxy-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)ethyl acrylate is 100:(3-5); the concentration of the two monomers in the prepolymerization solution is 8-10 mol / L.
8. A method for preparing a high-performance supramolecular hydrogel for hemostasis and wound closure according to claim 6 or 7, characterized in that, The tetrahydrobonded monomer 4-(6-(3-(6-methyl-4-oxy-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)ethyl acrylate is prepared according to the following steps: In the presence of dibutyltin dilaurate and chloroform, a mixture of 2(6-isocyanohexylaminocarbonylamino)-6-methyl-4[1H]pyrimidinone and 2-hydroxyethyl acrylate was stirred and reacted under nitrogen atmosphere and heating. After the reaction was completed, the mixture was cooled to room temperature, the residual solid was filtered off under reduced pressure, the filtrate was precipitated into n-hexane, the precipitate was collected and dried overnight under vacuum to obtain the hydrophobic tetrahydrobonded monomer 4-(6-(3-(6-methyl-4-oxy-1,4-dihydropyrimidin-2-yl)ureido)hexylcarbamoyloxy)ethyl acrylate (HE The reaction mixture (A-UPy) is prepared in the following manner: dibutyltin dilaurate is used as a catalyst at a concentration of 20-100 μL; chloroform is used as a solvent at a concentration of 100-300 mL; n-hexane is used as a precipitant at a concentration of 800-2000 mL; the molar ratio of 2(6-isocyanohexylaminocarbonylamino)-6-methyl-4[1H]pyrimidinone (UPy-NCO) to 2-hydroxyethyl acrylate (HEAA) is 1:(1.1-2), preferably 1:(1.1-1.5); the reaction temperature is 45-70 °C, preferably 50-60 °C; and the reaction time is 8-20 h, preferably 12-15 h.
9. A method for preparing a high-performance supramolecular hydrogel for hemostasis and wound closure according to claim 6 or 7, characterized in that, 2-Hydroxy-2-methyl-1-phenyl-1-propanone is selected as the photoinitiator, and its amount is 0.1-0.5 mol% of the sum of the two monomers, preferably 0.1-0.25 mol%. The photoinitiation polymerization time is 0.5-2 h, preferably 0.5-1 h. The photoinitiation polymerization temperature is room temperature, 20-30 degrees Celsius. The concentration of epigallocatechin gallate in the aqueous solution is 0.1%-0.8% w / v, preferably 0.5-0.8% w / v. The soaking time in the epigallocatechin gallate aqueous solution is 4-10 h, preferably 6-10 h. The temperature is room temperature, 20-30 degrees Celsius. The reaction vessel is a glass mold with silicone sheets spaced apart, and the thickness of the silicone sheets is 1.5-2 mm.
10. The application of the high-performance supramolecular hydrogel as described in any one of claims 1-5 in the preparation of hemostatic and / or wound repair materials.